Low Toe–Brachial Index Is Associated With Stroke Outcome Despite Normal Ankle–Brachial Index - Han, Minho; Kim, Young Dae; Lee, Ilhyung; Lee, Hyungwoo; Heo, Joonnyung; Lee, Hye Sun; Nam, Hyo Suk (Frontiers in Neurology, 2021)
Introduction: We investigated whether the toe–brachial index (TBI) is associated with stroke prognosis and evaluated this association in patients with normal ankle–brachial index (ABI). Methods: Acute ischemic stroke patients who underwent TBI measurements were enrolled. Poor functional outcome was defined as modified Rankin Scale score ≥ 3. Major adverse cardiovascular event (MACE) was defined as stroke recurrence, myocardial infarction, or death. A normal ABI was defined as 0.9 ≤ ABI ≤ 1.4. Results: A total of 1697 patients were enrolled and followed up for a median 39.7 (interquartile range, 25.7–54.6) months. During the period, 305 patients suffered MACE (18.0%), including 171 (10.1%) stroke recurrences. TBI was associated with hypertension, diabetes, atrial fibrillation, aortic plaque score, ABI, and brachial–ankle pulse wave velocity (all p values < 0.05). In multivariable logistic regression, TBI was inversely associated with poor functional outcome in all patients (OR 0.294, 95% confidence interval (CI) 0.114‒0.759), even in patients with normal ABI (OR 0.293, 95% CI 0.095‒0.906). In multivariable Cox regression, TBI < 0.6 was associated with stroke recurrence (HR 1.651, 95% CI 1.135‒2.400), all-cause mortality (HR 2.105, 95% CI 1.343‒3.298), and MACE (HR 1.838, 95% CI 1.396‒2.419) in all patients. TBI < 0.6 was also associated with stroke recurrence (HR 1.681, 95% CI 1.080‒2.618), all-cause mortality (HR 2.075, 95% CI 1.180‒3.651), and MACE (HR 1.619, 95% CI 1.149‒2.281) in patients with normal ABI. Conclusions: Low TBI is independently associated with poor short- and long-term outcomes in acute ischemic stroke patients despite normal ABI.